Cross-cultural adaptation of the Clinical Perfectionism Questionnaire (CPQ) for Brazilians - Rocha,Luiz Fellipe Dias da (2022)
Abstract The goals of this paper are the cross-cultural adaptation and psychometric properties evaluation of the Brazilian version of the Clinical Perfectionism Questionnaire (CPQ), a scale that measures the tendency of a person to pursue self-demanding standards and the subjective consequences provided by achieving them or not. The original instrument was translated to Portuguese and back-translated to English. The preliminary version was judged by one of the authors of the instrument and by Brazilian specialists, producing content validity indicators. The final version was applied to a sample of 250 Brazilian undergraduate students, aged from 18 to 60 years old (M=24.9, SD=8.63), mostly female (76%). In the Exploratory Factor Analysis, data have revealed a bidimensional structure, and the other psychometric properties, such as internal consistency and validity regarding other variables, have shown adequate to the instrument. Additional analyses of unidimensional congruence reinforced the multidimensionality of the measure.